The Effectiveness of Health Promotion Media for Expressed Breast Milk in Increasing the Knowledge of Working Mothers to Provide Exclusive Breast Milk in Purwakarta Regency, Indonesia - Armiyanti, Armiyanti (HM Publisher, 2024)
Background: Exclusive breastfeeding during the first six months of a baby's life is very important for the baby's health and development. However, many working mothers have difficulty providing exclusive breastfeeding because they have to return to work after giving birth. This research aims to determine the effectiveness of expressed breast milk health promotion media in increasing the knowledge of working mothers to provide exclusive breast milk in Purwakarta Regency. Methods: This research used a quasi-experimental design with a pre-test and post-test with control group design. The research sample was 60 working mothers who were divided into two groups, namely the intervention group (n=30) who were given expressed breast milk health promotion media and the control group (n=30) who were not given promotional media. Data were analyzed using the t-test. Results: The results showed that there was a significant difference (p<0.05) in the level of knowledge of working mothers about exclusive breastfeeding between the intervention group and the control group after the intervention. Conclusion: Expressed breast milk health promotion media is effective in increasing working mothers' knowledge about exclusive breastfeeding in Purwakarta Regency.